Community Participation in Management of Aquatic Animal Protected Area: A Case Study of Moo 1, Pa-khad Subdistrict, Singhanakhon District, Songkhla Province / การมีส่วนร่วมของชุมชนในการจัดการเขตอนุรักษ์สัตว์น้ำ:กรณีศึกษา หมู่ที่1 ตำบลป่าขาด อำเภอสิงหนคร จังหวัดสงขลา - and Jarunee Chiayvareesajja / อรทัย หนูสงค์ เยาวนิจ กิตติธรกุล และจารุณี เชี่ยววารีสัจจะ, Orathai Nusong, Jawani Kittitornkool (Journal of Community Development Research (Humanities and Social Sciences); Vol 9 No 2 (2559): May-August 2016, 2016)
บทคัดย่อ การศึกษาวิจัยนี้มุ่งศึกษาระดับและผลลัพธ์ของการมีส่วนร่วมในการจัดการเขตอนุรักษ์สัตว์น้ำ ของชุมชนหมู่ที่ 1 ตำบลป่าขาด อำเภอ สิงหนคร จังหวัดสงขลา ใช้การวิจัยแบบผสม (Mixed Method) โดยใช้วิธีการวิจัยเชิงปริมาณ ซึ่งเป็นการสัมภาษณ์โดยใช้แบบสอบถามกับตัวแทนครัวเรือน จำนวน 92 ครัวเรือน และวิธีการวิจัยเชิงคุณภาพ ได้แก่ การสัมภาษณ์แบบกึ่งโครงสร้าง การสังเกตการณ์แบบมีส่วนร่วม และการสนทนากลุ่ม กับแกนนำชุมชน จำนวน 12 คน ผลการวิจัย พบว่า การมีส่วนร่วมของชุมชนโดยรวมอยู่ในระดับมาก และระดับการมีส่วนร่วมในการรับผลประโยชน์อยู่ในระดับมากที่สุด รองลงมา คือ การมีส่วนร่วมในการค้นหาสาเหตุและปัญหา การมีส่วนร่วมในการปฏิบัติและดำเนินการ การมีส่วนร่วมในการติดตามและประเมินผล และการมีส่วนร่วมในการวางแผนเพื่อแก้ปัญหาอยู่ในระดับน้อยที่สุด ส่วนผลลัพธ์ของการมีส่วนร่วมในการจัดการฯ ทั้งในระดับครัวเรือนและชุมชนตามแนวคิดการทำมาหากิน พบว่า ทุนธรรมชาติเพิ่มมากที่สุด รองลงมา คือทุนมนุษย์ ทุนเงินตรา ทุนกายภาพ และทุนทางสังคมตามลำดับ   คำสำคัญ : การมีส่วนร่วมของชุมชน  การจัดการเขตอนุรักษ์สัตว์น้ำ  สงขลา  ทะเลสาบสงขลา  แนวคิดการทำมาหากิน   Abstract The research aims to study the level of community participation in management of aquatic animal protected area in Moo 1, Pa-khat Subdistrict, Singhanakhon District, Songkhla Province. A mixed method approach was employed, particularly a quantitative research method of using a questionnaire to interview representatives of ninety-two households. The qualitative research methods are semi-structured interview, participant observation and focus group discussion with core-team members of the community. It is found that the overall level of community participation is high, whereas the levels of participation stages can be ranked from the ones in obtaining benefits, implementations and practices, follow-up and monitoring, and planning for solutions respectively. Based on the concept of livelihoods approach, the outcomes of community participation at the household and community levels are ranked in the same way: increases in natural capital are the highest, then human capital, financial capital, physical capital and social capital respectively.   Keywords: Community Participation, Aquatic Animal Protected Area, Songkhla, Songkhla Lakeb Basin, Livelihoods Approach
Keywords: การมีส่วนร่วมของชุมชน การจัดการเขตอนุรักษ์สัตว์น้ำ สงขลา ทะเลสาบสงขลา แนวคิดการทำมาหากิน Community Participation, Aquatic Animal Protected Area, Songkhla, Songkhla Lakeb Basin, Livelihoods Approach